Code-switching in Yoruba newspapers as a reflection of the linguistic half-caste mode in Nigerian journalism - Salawu, Abiodun; Amenaghawon, Francis (Penerbit Universiti Kebangsaan Malaysia, 2023)
This paper examines code-switching as a language style of Yoruba newspapers, within the larger context of the day-to-day speech mannerisms of Nigerians. This linguistic mode is a result of culture mix and has encroached on the indigenous languages of the peoples, and the style (of the writings) of indigenous language media. The paper analyses the texts of Alaroye newspaper to demonstrate the phenomenon. Questions raised concerned the purpose of code-switching, as well as its effects on Yoruba language and influence on respondents’ interest in reading Alaroye. Survey and content analysis were the research designs used, while purposive sampling was preferred for the selection of seventy-five respondents to the questionnaire and six who were interviewed. Findings show that code-switching simplifies, aids comprehension, increases interest in indigenous language newspapers and accommodates the bilingualism of readers. Respondents agree that code-switching contributes to the linguistic half-caste mode of journalism and society.